Seminars In Education for Sustainability Aimed at Basic Education Teachers, as a Community Service Involving Postgraduate Students - José Alí Moncada Rangel; Lucía del Rocío Vásquez Hernández; Segundo Hernán Cadena Pulles (Journal of Sustainability Perspectives, 2023)
The teaching profession as a decisive role in the construction of sustainability as a civilizing model. The present community service project aims to implement a teacher training and updating process on sustainability issues and teaching tools for environmental education aimed at Basic Education teachers. The methodology was structured in two stages: 1.- Development of the teaching training and updating process, considering institutional needs and emerging disciplinary themes; 2.- Process evaluation. The seminar was developed with the participation of 112 teachers from different educational units in the Province and included conferences on Education for the SDGs, Education for the conservation of biodiversity and climate change, Education for responsible consumption and Horizontal Education. For their part, postgraduate students developed six workshops on didactic strategies such as simulation, comic strips, bulletin board, creation of terrariums, role playing and asking game. The evaluation applied after the seminar showed high acceptance of the activities carried out by trained teachers and postgraduate students. In the next training sessions, postgraduate students are expected to go to the educational communities of the schools to contextualize the training. Finally, the strategy made it possible to strengthen university community services that promote sustainability